Yupik materials, Phillips Fund Collection - Griffin, Dennis; Griffin, Eve; Jolles, Carol Zane; Woodbury, Anthony C. (1978)
The Yupik materials in the Phillips Fund collection consist of 5 items. Materials in this collection are listed alphabetically by last name of author. See materials listed under Griffin (Dennis and Eve), Jolles, and Woodbury.